Discrimination of different forms and oceanic regions of purpleback flying squid (Sthenoteuthis oualaniensis) based on stable isotopes and fatty acid composition - Zhu, Kai; Xu, Kaida; Zhu, Wenbin (Frontiers in Marine Science, 2024)
Pelagic cephalopods play a key role in the Chinese food supply. The market value of seafood frequently fluctuates based on its geographical origin and species, making it imperative to trace the origin and distinguish forms to guarantee food quality and accurate information. In this study, we used biochemical tracers, including stable isotope analysis and fatty acid composition profiling, to trace the origin of purpleback flying squid (Sthenoteuthis oualaniensis) from the Indian Ocean and South China Sea. We measured the δ 13 C and δ 15 N values and fatty acid (FA) contents in samples from different forms of S. oualaniensis obtained from these two oceanic regions. We analyzed the feeding and nutritional differences among these populations and conducted discriminant analysis. Significant regional and form differences were observed in both isotopic values and FA profiles in the muscle tissues of S. oualaniensis. Forms with larger sizes exhibited higher δ 13 C and δ 15 N values, potentially resulting from different feeding preferences and geographical environments. The discriminant analysis revealed that isotopic composition could effectively distinguish individuals from different oceanic regions, whereas FA composition was more effective in distinguishing different forms within the same oceanic region. The combination of isotopes and FAs could accurately discriminate S. oualaniensis of different forms and from different oceanic regions, achieving a discrimination accuracy of 100%. This study provides a reference for tracing the origin of pelagic cephalopods with complex form structures.